Factor Analysis as a Tool Supporting STEEPVL Approach to the Identification of Driving Forces of Technological Innovation. (2017) - Nazarko, Joanicjusz; Ejdys, Joanna; Halicka, Katarzyna; Nazarko, Łukasz; Kononiuk, Anna; Olszewska, Anna
Abstract: The purpose of the paper is to present the methodological basis and an example of factor analysis supporting STEEPVL analysis in the identification of driving forces of technology development in foresight studies. The proposed approach allows for the identification of a limited number of the most significant driving forces of technology development. The practical implications of the methodological considerations are presented in the paper in a form of a case study describing the combination of STEEPVL and factor analysis in the project entitled "Technological Foresight «NT FOR Podlaskie 2020». Regional Strategy of Nanotechnology Development".